Juvenile Dermatomyositis and Diffuse Cutaneous Systemic Sclerosis Overlap - Shatnawi, Hani; Ailabouni, Dona; Shatnawi, Ahmad Mohammad; Makahleh, Faisal Mohammad Hussain; AlBalawi, Bader; Namas, Rajaie (Ibnosina Journal of Medicine and Biomedical Sciences, 2023)
The overlapping nature of autoimmune diseases makes diagnosing and stratifying prognosis extremely difficult. Scleromyositis, the most common overlap syndrome, is typically seen in adults and is rarely seen in children. An overlap syndrome like scleromyositis would have clinical features of at least two connective tissue diseases (juvenile dermatomyositis and systemic sclerosis). Furthermore, the presence of anti-PM/Scl antibodies is critical. We describe a patient who presented with widespread skin tightening, hoarseness of voice, dysphagia, and muscle weakness that had been present for 6 months. The patient was diagnosed with overlap juvenile scleromyositis (scleroderma-dermatomyositis overlap). In practice, distinguishing this syndrome from dermatomyositis and scleroderma is critical.
Keywords: juvenile dermatomyositis; diffuse systemic sclerosis; scleroderma; Raynaud's phenomenon; connective tissue disease; overlap syndrome; scleromyositis; interstitial lung disease